2017
DOI: 10.15406/jabb.2017.04.00093
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimization of Dilute Acid Hydrolysis of Wood Sawdust for Lactic Acid Production

Abstract: Abbreviations: SW, sawdust wood; CCD, central composite design; LAB, lactic acid bacteria; L-LDH, L-lactate dehydrogenase; RSM, response surface methodology; 3D, 3-dimensional; MSW, meranti wood sawdust; OFI, Opuntia ficus indica IntroductionLactic acid has a wide application in food, pharmaceutical, leather, cosmetic applications, textile, and polylactic acid industries.1-3 Lactic acid can be produced either by fermentation or by chemical synthesis. But the biotechnological fermentation process has received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…There have been a number of reports describing the strategy of using a combination of dilute acid/alkaline pretreatment and enzymatic hydrolysis for cellulosic biomass saccharification [43,44,46,47]. Alkaline pretreatment and enzymatic hydrolysis of wheat straw (50 g/L) can generate a reducing sugar of 13.82 g/L [43], and dilute acid hydrolysis followed by enzymatic hydrolysis for wood sawdust could generate glucose at 8.68 g/L [48]. However, few studies have reported the saccharification of marine algae.…”
Section: The Effect Of Cellulase Hydrolysis On Marine Algae Saccharifmentioning
confidence: 99%
“…There have been a number of reports describing the strategy of using a combination of dilute acid/alkaline pretreatment and enzymatic hydrolysis for cellulosic biomass saccharification [43,44,46,47]. Alkaline pretreatment and enzymatic hydrolysis of wheat straw (50 g/L) can generate a reducing sugar of 13.82 g/L [43], and dilute acid hydrolysis followed by enzymatic hydrolysis for wood sawdust could generate glucose at 8.68 g/L [48]. However, few studies have reported the saccharification of marine algae.…”
Section: The Effect Of Cellulase Hydrolysis On Marine Algae Saccharifmentioning
confidence: 99%
“…By default, the high levels of the factors are coded +1, and the low levels are coded −1. Plus Signs (+) represent a synergistic relationship, while minus signs (−) indicate antagonism between variables [ 27 ]. The quadratic equations obtained by regression analysis are presented in equations (3) , (4) ), for the content of PC and RS.…”
Section: Resultsmentioning
confidence: 99%
“…This is perceived through the arrangement of the points grouped around the regression line. In addition, since least-squares residuals are an important tool for judging the fit of the model [ 27 ], Fig. 3 , Fig.…”
Section: Resultsmentioning
confidence: 99%